DAMPAK IMPLEMENTASI PSAK NO. 73 TERHADAP LABA DAN PAJAK - Nadien, Adam Dhiyaulhaq; Liza Alvia (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
This study investigates the implementation of PSAK 73 and its implications for profit and tax reporting at PT ABC. Using a case study approach, data were collected through observations, interviews, and document analysis. The research outlines how PT ABC identifies, records, measures, presents, and discloses lease transactions in accordance with PSAK 73. The standard’s implementation impacts profit calculation due to increased depreciation and interest expenses. Additionally, differences between accounting standards and tax regulations in lease treatment result in fiscal profit, used for tax purposes, differing from accounting profit.